Bimbingan Konseling Bagi Anak Cerdas Istimewa Dan Kesulitan Belajar (Disleksia, Disgrafia, Diskalkulia) - Rafael Lisinus Ginting; Apri Yanti Kasilda Siburian; Theresia Elizasabaet Sianturi; Shyndy Monika Sianturi; Natalia Br Ginting; Sekar Ayu Pratiwi (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This research aims to examine guidance and counseling for children with special intelligence and learning disorders (dyslexia, dysgraphia, dyscalculia). This research uses a type of research in the form of library research. The results of this research are that counseling services can be provided for special intelligence/gifted children such as enrichment, acceleration, special grouping. Then the implementation of guidance for children with learning disabilities (Learning Disabilities) was also studied, starting with understanding the characteristics of children, becoming familiar with the assessment instruments used to determine the type and level of children's learning difficulties in order to understand and communicate to the expert team about children's learning problems.